Introduction to the Special Section on Social Neuroscience: Promise and Caveats. - Harmon-Jones, Eddie; Devine, Patricia G. (Journal of Personality & Social Psychology, 2003)
This special issue of the Journal of Personality and Social Psychology: Attitudes and Social Cognition is devoted to theory and research at the interface of social psychology and neuroscience. The 5 empirical articles represent the theoretical and methodological breadth of issues considered by social neuroscientists. The methods span brain lesion work to neuroendocrinology to psychophysiological indicators of brain activity to functional magnetic resonance imaging indicators of brain activity. The remaining 2 articles consider explicitly some of the promises and pitfalls of social neuroscience; these authors, although noting the power of neuroscience methods, remind readers of the serious challenges posed in trying to examine the biological processes underlying or associated with social psychological phenomena. These articles help to reveal the richness of social neuroscience and the power of neuroscientific methods to address processes and mechanisms that would not be possible with traditional social psychology methods. Reprinted by permission of the publisher.